The effectiveness of promotion towards customer awareness on ASG scheme in ASNB Kuala Lumpur / Siti Fadilah Othman - Othman, Siti Fadilah (Faculty of Business and Management, 2007)
Nowadays, most Malaysians are more interested in investing their money with the intention to increase their savings. This is because they are more concerned towards the future of themselves in terms of family, children as well as a step for protection if the rainy days come unexpectedly. Therefore, as an organization that expert in the field of investment, Amanah Saham Nasional Berhad offers this service in fulfilling the demand of Malaysians. Amanah Saham Nasional Berhad is offering several types of unit trust that promise profits for every single cent that customer invest in Amanah Saham Nasional Berhad. The most popular unit trust is Amanah Saham Bumiputera which is the 'must have' unit trust by investors. The question is how far has Amanah Saham Nasional Berhad go in positioning their investor's mind to invest especially for Bumiputera. There are grouses that many Bumiputera does still not aware about Amanah Saham Nasional Berhad products (unit trust). This is because they do not know what are benefits and functions of Amanah Saham Nasional Berhad. Therefore, this study will discuss on how to increase savings among Bumiputera and to determine the understanding of Bumiputera about Amanah Saham Nasional Berhad. This study will only focus on the relationship between Amanah Saham Gemilang (which is Amanah Saham Nasional Berhad products -unit trust) and Bumiputera.